2017
DOI: 10.1017/s0890060417000191
|View full text |Cite
|
Sign up to set email alerts
|

A decision model for making decisions under epistemic uncertainty and its application to select materials

Abstract: This study deals with both a decision model for making decisions under epistemic uncertainty and how to use it for selecting optimal materials under the same uncertainty. In particular, the proposed decision model employs a set of possibilistic objective functions defined by fuzzy numbers to handle a set of conflicting criteria. In addition, the model can calculate the compliance of a piece of decision-relevant (imprecise) information with a given objective function. Moreover, the model is capable to aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…One challenge is the epistemic uncertainty, i.e., the lack of knowledge on how to interpret the results and how to design further steps, e.g., simulation experiments, and also the imprecise and coarsedata and information for the modeling and parameterization of simulation models. Decision models can help here [59].…”
Section: Discussionmentioning
confidence: 99%
“…One challenge is the epistemic uncertainty, i.e., the lack of knowledge on how to interpret the results and how to design further steps, e.g., simulation experiments, and also the imprecise and coarsedata and information for the modeling and parameterization of simulation models. Decision models can help here [59].…”
Section: Discussionmentioning
confidence: 99%
“…Purpose Techniques Yazdani [36] Material selection AHP, FARE * and WASPAS * Shahinur et al [37] Material selection DSS and fuzzy analysis Jadid [38] Material selection DSS Venkata and Davim [39] Material selection AHP and TOPSIS * Sefair et. al.…”
Section: Referencesmentioning
confidence: 99%
“…The sole attention of this paper is about the MADM framework. MADM approaches are already well demonstrated that addresses the uncertainty by considering a set of alternatives with uncertain values for the attributes or criteria of the alternatives (Wallenius et al ., 2008; Shahinur et al ., 2017). The basic steps in all MADM approaches are generally considered as: Decision matrix is the discrete decision space where a finite set of alternatives is expressed by its performance ratings in multiple attribute or criteria. Weightage or priority is assigned to each criterion according to the design requirements to satisfy the customer's demands and desires.…”
Section: Materials Selectionmentioning
confidence: 99%
“…Shahinur et al . (2017) judiciously introduced the fuzzy logic to select the material for vehicle body and the aluminum alloys are chosen as the best materials. Cryogenic storage tank materials are analyzed by WPM (Dehghan-Manshadi et al ., 2007), TOPSIS (Jahan et al ., 2012a), MOORA (Karande and Chakraborty, 2012), Fuzzy logic (Khabbaz et al ., 2009), and the preeminent material is considered as Austenitic steel (SS 301-FH).…”
Section: Materials Selectionmentioning
confidence: 99%